Time dependent impact of perinatal hypoxia on growth hormone, insulin-like growth factor 1 and insulin-like growth factor binding protein-3 - Kartal, Ömer; Aydınöz, Seçil; Kartal, Ayşe Tuğba; Keleştemur, Taha; Çağlayan, Ahmet Burak; Beker, Mustafa Çağlar; Karademir, Ferhan; Süleymanoğlu, Selami; Kul, Mustafa; Yuluğ, Burak; Kılıç, Ertuğrul (Springer/Plenum Publishers, 2016)
Hypoxic-ischemia (HI) is a widely used animal model to mimic the preterm or perinatal sublethal hypoxia, including hypoxic-ischemic encephalopathy. It causes diffuse neurodegeneration in the brain and results in mental retardation, hyperactivity, cerebral palsy, epilepsy and neuroendocrine disturbances. Herein, we examined acute and subacute correlations between neuronal degeneration and serum growth factor changes, including growth hormone (GH), insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) after hypoxic-ischemia (HI) in neonatal rats. In the acute phase of hypoxia, brain volume was increased significantly as compared with control animals, which was associated with reduced GH and IGF-1 secretions. Reduced neuronal survival and increased DNA fragmentation were also noticed in these animals. However, in the subacute phase of hypoxia, neuronal survival and brain volume were significantly decreased, accompanied by increased apoptotic cell death in the hippocampus and cortex. Serum GH, IGF-1, and IGFBP-3 levels were significantly reduced in the subacute phase of HI. Significant retardation in the brain and body development were noted in the subacute phase of hypoxia. Here, we provide evidence that serum levels of growth-hormone and factors were decreased in the acute and subacute phase of hypoxia, which was associated with increased DNA fragmentation and decreased neuronal survival.
WOS: 000379187900010
PubMed ID: 26943480
Keywords: Perinatal Hypoxia; Brain Injury; Apoptosis; Serum GH; IGF-1; IGFBP-3 Levels